Mengapa Generasi Z di Bogor Memilih QRIS Tinjauan dari Gaya Hidup hingga Sikap Keuangan - Zeze Zakaria Hamzah (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2025)
Digital transformation in Indonesia's financial sector has accelerated the adoption of cashless payment systems, with QRIS (Quick Response Code Indonesian Standard) as the main innovation since its introduction by Bank Indonesia in 2019. Generation Z, as a digital native group, is the dominant user of QRIS due to their preference for fast, practical, and connected services. This study aims to empirically analyze the influence of lifestyle, ease of use, trust, and financial attitudes on the decision to use QRIS by Generation Z in Bogor Regency, as well as test the role of financial literacy as a moderation variable. The research approach uses quantitative methods through inferential statistical analysis. The results showed that only the variables of ease of use and financial attitude had a significant effect on the decision to use QRIS, with a significance value of < 0.05 and t calculated > t table. These findings reinforce the Technology Acceptance Model (TAM) model, which emphasizes the importance of the perception of convenience in driving the adoption of digital payment technology. Meanwhile, the variables of lifestyle and trust did not have a significant effect, which may be due to the level of general trust that has been formed in QRIS and the digital lifestyle of respondents who have not fully developed. These results confirm the need to develop a more intuitive user experience and increase education related to digital financial literacy to strengthen the sustainable use of QRIS among Generation Z.